Emergency service units in Turkey don't have enough resources to implement the one- hour sepsis bundle components and sepsis guidelines recommendations, 238 emergency department directors opinion (Annals of Medical Research, 2021)
Aim: Aim of this study is to investigate whether emergency rooms in Turkey have sufficient resources to treat sepsis patients. Sepsis has a high incidence and can result in multiple organ failure and death within hours if not rapidly intervened. Septic patients, are generally first admitted to the emergency departments. In the management of these patients, it is very important to have well -knowledged team and enough resources.Materials and Methods: A questionnaire regarding whether education and emergency room resources were sufficient to diagnose and treat sepsis was e-mailed to the directors of emergency department. Data collection took place from December 17, 2019 to December 27, 2019.Results: The study included 238 participants, of who worked in university hospitals, training and research hospitals, state hospitals, and inprivate hospitals. The first health care professional to examine emergency patients was a physician in 162 of the hospitals, and a nurse in 76. Sepsis treatment was delayed due to laboratory test delays in 77 hospitals, triage patient non-determinability in 62, and diagnosis delays in 33. Staffing was inadequate, with 54 participants reporting difficulties in reaching an emergency medicine physician, 124 in reaching an infectious disease physician, 203 in reaching a microbiologist, and 125 in reaching an intensive care physician.Conclusion: Emergency rooms in Turkey suffer from limited resources to properly implement sepsis treatment guidelines and bundles. Resources should be improved.
Keywords: Emergency room; implementation; resources; sepsis bundle; Turkey